Analysis of The Impact of Digital Transformation and Business Capital on Income - Putra, Yoshua Ardy; Mariam , Iis; Syafganti, Imam; Sukaesih, Ina; Sofa, Nidia; Mubarak, Fauzi; Hadikusuma, Riza; Chandra, Yanita Ella Nilla (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Digital transformation has changed the business landscape globally, including for Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector. This study aims to analyze the effect of digital transformation and business capital on the income of culinary MSMEs in Baktijaya Village, Depok City. This research approach uses a quantitative method with data collection techniques through questionnaires to culinary MSME respondents in Depok City. The collected data were analyzed using PLS-SEM with the help of SmartPLS. The results of the study show that digital transformation has a positive and significant effect on the income of culinary MSMEs with T-Statistics value of 3.517. In addition, business capital also has a positive and significant effect on business income with T-Statistics value of 5.431. This study contributes to the understanding that the application of information and communication technology and adequate business capital can improve the financial performance of culinary MSMEs, increase operational efficiency, and market reach. The practical implications of this study are the importance of integrating digital technology and optimizing business capital in MSME development strategies in the current digital era, in order to encourage sustainable growth and increase business competitiveness in an increasingly competitive market. MSMEs must be flexible and keep up with the times to continue to maintain their existence and develop their businesses by digitizing.